Peran Fucoidan Terhadap Angiogenesis - Muhammad Yusran; Muhammad Irsan Saleh; Ernawati Sinaga; Ramzi Amin (Universitas Malahayati, 2026)
ABSTRACT Angiogenesis is a tightly regulated biological process that supports tissue growth and wound healing. Dysregulation of this process may lead to various pathological conditions, including cancer, cardiovascular diseases, and diabetic retinopathy. Fucoidan is a sulfated polysaccharide derived from several marine species, such as brown seaweeds and sea cucumbers. Fucoidan has been reported to possess therapeutic potential in diseases associated with angiogenesis.To elucidate the role of fucoidan in the modulation of angiogenesis, both as a pro-angiogenic and anti-angiogenic agent across various pathological conditions. This article was prepared through a literature search conducted in EMBASE/Elsevier, Google Scholar, PubMed, ScienceDirect, and the Cochrane Review for publications from 2015 to 2025. The search terms included “angiogenesis”, “fucoidan”, “fucoidan AND (pro-angiogenic OR proangiogenic)”, and “fucoidan AND (anti-angiogenic OR antiangiogenic)”. Inclusion criteria comprised English-language, relevant full-text publications (2015–2025), including both original research articles and review papers. The synthesized evidence indicates that the effects of fucoidan on angiogenesis are influenced by molecular weight, degree of sulfation, source material, extraction methods, dosage, and disease context. Low-molecular-weight fucoidan tends to exert pro-angiogenic effects by enhancing endothelial cell proliferation and migration through the PI3K/AKT and AKT/Nrf2/HIF-1α signaling pathways, thereby potentially accelerating wound healing. In contrast, high-molecular-weight fucoidan may exhibit anti-angiogenic properties by suppressing VEGF and HIF-1α expression, inhibiting vascular tube formation, and modulating mechanisms associated with tumor progression, suggesting its potential application as a therapeutic target in cancer. Fucoidan is a context-dependent modulator of angiogenesis that may exert either pro- or anti-angiogenic effects depending on its physicochemical characteristics and biological context. Keywords: Angiogenesis, Fucoidan, Pro-Angiogenik, Anti-Angiogenik. ABSTRAK Angiogenesis merupakan proses biologis yang diatur secara ketat untuk mendukung pertumbuhan jaringan dan proses penyembuhan luka. Adanya disregulasi pada proses ini dapat menyebabkan berbagai kondisi patologis seperti kanker, penyakit kardiovaskular dan retinopati diabetik. Fucoidan adalah polisakarida sulfat yang berasal dari beberapa spesies laut, seperti ganggang cokelat dan teripang. Fucoidan dilaporkan memiliki potensi terapeutik pada penyakit yang terkait dengan angiogenesis. Untuk menguraikan peran fucoidan dalam modulasi angiogenesis, baik sebagai agen pro-angiogenik maupun anti-angiogenik pada berbagai kondisi patologis. Penulisan artikel ini dilakukan melalui penelusuran literatur pada EMBASE/Elsevier, Google Scholar, PubMed, ScienceDirect, dan Cochrane Review untuk publikasi tahun 2015–2025. Kata kunci yang digunakan meliputi “angiogenesis”, “fucoidan”, “fucoidan AND (pro-angiogenic OR proangiogenic)”, dan “fucoidan AND (anti-angiogenic OR antiangiogenic)”. Kriteria inklusi mencakup publikasi berbahasa Inggris dengan full-text yang relevan (2015–2025), termasuk artikel original maupun review. Hasil sintesis menunjukkan bahwa efek fucoidan terhadap angiogenesis dipengaruhi oleh berat molekul, derajat sulfatasi, sumber bahan, metode ekstraksi, dosis, serta kondisi penyakit. Fucoidan dengan berat molekul rendah cenderung bersifat pro-angiogenik melalui peningkatan proliferasi dan migrasi sel endotel melalui jalur PI3K/AKT dan AKT/Nrf2/HIF-1α, sehingga berpotensi mempercepat penyembuhan luka. Sebaliknya, fucoidan dengan berat molekul tinggi dapat bersifat anti-angiogenik, dengan menekan ekspresi VEGF dan HIF-1α, menghambat pembentukan tabung vaskular, serta memodulasi mekanisme yang terkait progresivitas tumor, sehingga berpotensi dimanfaatkan sebagai target terapi kanker. Fucoidan merupakan modulator angiogenesis yang dapat bersifat pro- maupun anti-angiogenik tergantung karakteristik dan konteks biologisnya. Kata Kunci: Angiogenesis, Fucoidan, Pro-Angiogenik, Anti-Angiogenik.